Performance evaluation of external fired hybrid solar gas-turbine power plant in Colombia using energy and exergy methods (2020)
Hydro and thermal generation power systems dominate the Colombian electricity sector. In 2017, Colombia installed electrical generation capacity was 16.8 GW. Renewable energy sources represent at least 85% of the total generation, being hydro the principal source. Several alternatives had been evaluated through the years to improve the Colombian energy matrix and capacity, including solar photovoltaic and wind plants; despite that, no consensus about the appropriate solution in terms of the available resource, energy demand, and energy mix has been attained. Thermosolar power plants arise as an alternative to produce energy in sites where nearly constant solar irradiance throughout the year is available, which is the case for most Colombian cities. This work concerned the evaluation of a single-stage hybrid Central Solar Power (CSP) plant at a location on the Caribbean Colombian coast. The study is focused on establishing the effect of local environmental conditions (ambient temperature and solar resource availability), as well as some operational cycle parameters (heat exchanger effectiveness and the system pressure ratio) on the CSP plant performance. Additionally, site emplacement conditions, i.e., proximity to the power grid, presence of conventional thermal power plants, proximity to principal cities, and availability of natural gas), are also considered to attain the factors that might constrain the plant optimal operating conditions. The CSP plant and the Direct Normal Irradiance (DNI) model results obtained fitted in good agreement the experimental data from the literature used for validation. Results have shown a global plant efficiency of 35% without solar resource which is reduced to 30% when solar contribution attains its maximum value at midday. Additionally, fuel-saving per day varies between 9.21% and 6.3% during the months of maximum and minimum global radiation, respectively. Finally, that the combustion chamber, its associated heat exchanger and the one that is in direct exchange with the surroundings, are the components with the most exergy destruction, as expected. From the above, it is sensible to explore alternatives regarding different working fluids that could be used in lower temperature cycles and other applications for heat recovery.